Theatre, performance and technology the development and transformation of scenography - Baugh, Christopher (Theatre & performance practices, 2013)
Throughout history, scenography has played a significant role in theatre, always drawing upon the latest technologies of manufacture and control. In the twenty-first century, it is fast becoming an artistic practice in its own right, engaging with audiences in varied ways. Christopher Baugh considers how change in scenographic identity has impacted upon the place and meaning of performance over the past 300 years. Thoroughly revised and updated, the second edition discusses: moving light technologies; the Internet as a platform of performance; urban scenography; scenography's role in the creation of memory; the development of scenography as a collaborative practice.